Morphological variability, molecular phylogeny, and biological characteristics of the nematophagous fungus Duddingtonia flagrans. (23rd April 2019) - Wang, Bo‐Bo; Zhang, Nan; Gong, Peng‐Tao; Li, Jian‐Hua; Yang, Ju; Zhang, Hong‐Bo; Zhang, Xi‐Chen; Cai, Kui‐Zheng
Abstract: This study aims to investigate the molecular phylogenetic analysis, morphological variability, nematode‐capturing ability, and other biological properties of Chinese Duddingtonia flagrans isolates. We isolated 13 isolates of D. flagrans and found features that have never been reported before, such as two to three septa incluing club‐shaped conidia. Meanwhile, we conducted molecular phylogenetic analysis of the seven isolates and tested the radical growth of the isolates under different pH values, temperatures, and media. The capturing ability against infective larvae (L3) of Cooperia spp. in yak was detected in vitro. Finally, one isolate was selected for scanning electron microscopy (SEM) to investigate the trap formation process. The fungal sequence was obtained and submitted to GenBank (Accession no. KY288614.1, KU881774.1, KP257593.1, KY419119.1, MF488979.1, MF488980.1, and MF488981.1), and the tested isolates were identified as D. flagrans . Except for three isolates, the radial growth of the other isolates on 2% corn meal agar and 2% water agar exhibited faster growth than on other media. The fungus could not grow at 10 and 40°C but grew within 11 to 30°C. Moreover, it did not grow at pH 1–3 and 13–14, but instead at pH 4–12. In the in vitro experimental, L3s were reduced by 94.36%, 88.15%, and 91.04% for SDH035, DH055, and F088, respectively. SEM results showed that at 8 hr post addition of nematodes, some of the latter were captured. In the later stages of the interaction of the fungus with nematodes, a large number of chlamydospores were produced, especially on the predation trap. Results of the present study provided information about the molecular phylogenetic analysis, morphological variability, nematode‐capturing ability, and other biological properties of Chinese Arthrobotrys flagrans isolates before administering them for biocontrol.